Lossyness: Material Loss in the Cloud or Digital Ekphrasis. - ZIMMER, ZAC (Revista Hispánica Moderna (0034-9593), 2018)
The article reports on digital ekphrasis as an important tool to theorize the materiality and corporality of transcoding in the literary field. Topics discussed include a literary project that resides at the margins of textual materiality; Krissy Wilson's Tumblr "The Art of Google Books" that recontextualizes the images created during Google’s book digitization project as photographic objects to create an online exhibition of failed digitization; and opinion that Wilson’s project shows the material hand behind the process of digitization.